Examining the Reticulocyte Preference of Two Plasmodium berghei Strains during Blood-Stage Malaria Infection - Thakre, Neha; Fernandes, Priyanka; Mueller, Ann-Kristin; Graw, Frederik (Frontiers in Microbiology, 2018)
The blood-stage of the Plasmodium parasite is one of the key phases within its life cycle that influences disease progression during a malaria infection. The efficiency of the parasite in infecting red blood cells (RBC) determines parasite load and parasite-induced hemolysis that is responsible for the development of anemia and potentially drives severe disease progression. However, the molecular factors defining the infectivity of Plasmodium parasites have not been completely identified so far. Using the Plasmodium berghei mouse model for malaria, we characterized and compared the blood-stage infection dynamics of PbANKA WT and a mutant parasite strain lacking a novel Plasmodium antigen, PbmaLS_05, that is well conserved in both human and animal Plasmodium parasite strains. Infection of mice with parasites lacking PbmaLS_05 leads to lower parasitemia levels and less severe disease progression in contrast to mice infected with the wildtype PbANKA strain. To specifically determine the effect of deleting PbmaLS_05 on parasite infectivity we developed a mathematical model describing erythropoiesis and malarial infection of RBC. By applying our model to experimental data studying infection dynamics under normal and drug-induced altered erythropoietic conditions, we found that both PbANKA and PbmaLS_05 (-) parasite strains differed in their infectivity potential during the early intra-erythrocytic stage of infection. Parasites lacking PbmaLS_05 showed a decreased ability to infect RBC, and immature reticulocytes in particular that are usually a preferential target of the parasite. These altered infectivity characteristics limit parasite burden and affect disease progression. Our integrative analysis combining mathematical models and experimental data suggests that deletion of PbmaLS_05 affects productive infection of reticulocytes, which makes the corresponding PbmaLS_05 (-) parasite strain a useful tool for the analysis of RBC preferences on the development of severe disease outcomes in malaria.